Sea Power Indonesia Related to Geopolitics in The South China Sea and Geoeconomics in the North Natuna Sea Sloc & Slit - Rahma Agun Aulal Muna; Abdul Rivai Ras; Rudiyanto; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This article talks about Indonesia's sea power from a geopolitical perspective in the South China Sea and geoeconomics (Sea Lane of Trade/SLoT) as well as communication lines (Sea Lane of Communication/SLoC) in the North Natuna Sea. The theory used to analyze this journal is the concept of sea power. This article also dissects the wealth of natural resources as well as the strategic position of the country which needs to be utilized optimally for the national interest. The research method used is the descriptive qualitative method. The results of the analysis show that Indonesia has extraordinary natural resource potential for the future. Indonesia's strategic location must be fully utilized and security must be maintained. Keywords: Sea Power, Geopolitics, Geoeconomics, South China Sea, North Natuna Sea SLOC and SLIT